Illiquidity premium in asset returns : an empirical analysis of various liquidity measures to determine the best measure of liquidity on the Johannesburg Stock Exchange - Herbst, Wynand (University of Pretoria, 2018)
Mini Dissertation (MBA)--University of Pretoria, 2017.